Patient Characteristics and Outcomes of Outpatient Parenteral Antimicrobial Therapy: A Retrospective Study - Marie Yan; Marion Elligsen; Andrew E. Simor; Nick Daneman (Canadian Journal of Infectious Diseases and Medical Microbiology)
Outpatient parenteral antimicrobial therapy (OPAT) is a safe and effective alternative to hospitalization for many patients with infectious diseases. The objective of this study was to describe the OPAT experience at a Canadian tertiary academic centre in the absence of a formal OPAT program. This was achieved through a retrospective chart review of OPAT patients discharged from Sunnybrook Health Sciences Centre within a one-year period. Between June 2012 and May 2013, 104 patients (median age 63 years) were discharged home with parenteral antimicrobials. The most commonly treated syndromes included surgical site infections (33%), osteoarticular infections (28%), and bacteremia (21%). The most frequently prescribed antimicrobials were ceftriaxone (21%) and cefazolin (20%). Only 56% of the patients received follow-up care from an infectious diseases specialist. In the 60 days following discharge, 43% of the patients returned to the emergency department, while 26% required readmission. Forty-eight percent of the return visits were due to infection relapse or treatment failure, and 23% could be attributed to OPAT-related complications. These results suggest that many OPAT patients have unplanned health care encounters because of issues related to their infection or treatment, and the creation of a formal OPAT clinic may help improve outcomes.